La Crosse Virus Neuroinvasive Disease in Children: A Contemporary Analysis of Clinical/Neurobehavioral Outcomes and Predictors of Disease Severity. (24th May 2022) - Boutzoukas, Angelique E; Freedman, Daniel A; Koterba, Christine; Hunt, Garrett W; Mack, Kathy; Cass, Jennifer; Yildiz, Vedat O; de los Reyes, Emily; Twanow, Jaime; Chung, Melissa G; Ouellette, Christopher P
Abstract: Background: La Crosse virus (LACV) is the most common neuroinvasive arboviral infection in children in the United States. However, data regarding predictors of disease severity and neurologic outcome are limited. Additionally, long-term neurologic and neurobehavioral outcomes remain relatively sparse. Methods: This was a single-center, retrospective cohort study, followed by recruitment for a cross-sectional analysis of long-term neurobehavioral outcomes, among children aged 0–18 years with proven or probable LACV neuroinvasive disease (LACV-ND) between January 2009 and December 2018. Case ascertainment was assured by International Classification of Diseases, Ninth and Tenth Revision, Clinical Modification codes cross-referenced with laboratory results detecting LACV. Demographics, diagnostics, radiographs, and outcomes were evaluated. Recruitment of patients with prior diagnosis of LACV-ND occurred from January 2020 to March 2020, with assessment performed by validated pediatric questionnaires. Results: One-hundred fifty-two children (83 males; median age, 8 years [interquartile range, 5–11.5 years]) were diagnosed with proven (n = 61 [47%]) and probable (n = 91 [60%]) LACV-ND. Sixty-five patients (43%) had severe disease. Altered mental status (AMS) (odds ratio [OR], 6.36 [95% confidence interval CI, 2.03–19.95]; P = .0002) and seizures at presentation (OR, 10.31 [95% CI, 3.45–30.86]; P = .0001) were independent predictors of severe disease. Epileptiform discharges on electroencephalogram (EEG) were independently associated with epilepsy diagnosis at follow-up (OR, 13.45 [95% CI, 1.4–128.77]; P = .024). Fifty-four patients were recruited for long-term neurobehavioral follow-up, with frequent abnormal assessments identified (19%–54%) irrespective of disease severity. Conclusions: Severe disease was observed frequently among children with LACV-ND. Seizures and AMS at presentation were independent predictors of severe disease. EEG may help determine long-term epilepsy risk. Long-term neurobehavioral issues are frequent and likely underrecognized among children with LACV-ND. Abstract : Altered mentation and seizures at presentation are reliable predictors of severe La Crosse Virus neuroinvasive disease (LACV-ND). Epileptiform discharges on electroencephalogram during hospitalization is predictive of long-term epilepsy diagnosis. Children with LACV-ND have long-term neurobehavioral problems, which may be underrecognized.